PMEPA1 and NEDD4 control the proton production of osteoclasts by regulating vesicular trafficking. Issue 2 (23rd January 2021) - Hirata, Hirohito; Xu, Xianghe; Nishioka, Kenichi; Matsuhisa, Fumikazu; Kitajima, Shuji; Kukita, Toshio; Murayama, Masatoshi; Urano, Yasuteru; Miyamoto, Hiroshi; Mawatari, Masaaki; Kukita, Akiko
Abstract: Osteoclast bone resorption activity is critically regulated to maintain bone homeostasis. Osteoclasts resorb bone by producing protons and acid hydrolase via lysosomal secretion, however, a detailed mechanism remains elusive. PMEPA1 is a vesicular membrane protein, which binds to the NEDD4 family member of ubiquitin ligases. We have previously reported that Pmepa1 is highly expressed in bone resorbing osteoclasts, and regulates bone resorption. Here, we investigated the mechanism of bone resorption regulated by PMEPA1. Mutant mice lacking NEDD4‐binding domains of PMEPA1 displayed enhanced bone volume, and reduced bone resorption activity in comparison with those of WT mice. Analysis with pH‐sensitive fluorescence probe revealed that proton secretion from osteoclasts significantly decreased in Pmepa1 mutant osteoclasts. Immunofluorescence analysis revealed that PMEPA1 was colocalized with NEDD4, V0A3, and V0D2 subunits of vacuolar ATPase, which regulate the proton production of osteoclasts. In addition, Nedd4 knockdown reduced bone resorption and proton secretion of osteoclasts. Furthermore, Pmepa1 mutation and Nedd4 knockdown altered the cytoplasmic distribution of components of V‐ATPase and expression of autophagy‐related proteins, suggesting that lysosomal secretion is affected. Collectively, these findings indicate that PMEPA1 controls proton secretion from osteoclasts via NEDD4 by regulating vesicular trafficking, and NEDD4 is an important regulator of bone resorption.